The Influence of Job Satisfaction and Organizational Commitment on Turnover Intentions Hospital Nurses - Hasnah, Caturia Mei; Panjaitan, Nurmala K.; Ekananta, Arry (School of Business, Bogor Agricultural University (SB-IPB), 2023)
Nurses are human resources with the most significant number of all human resources in hospitals and a component that influences the quality of hospital services. Health services can be adequately provided if human resources such as nurses are met in quality and quantity. Currently, a private hospital in Bogor district still needs help completing the number of nurses requirement. Highly turnover rate of nurses occurred in the period 2020 to 2022. This study aims to analyze the influence of job satisfaction and organizational commitment on nurses' turnover intentions. Data collection was carried out using a questionnaire and interviews. This study uses the census method, the nurses who will be respondents are all nurses with a minimum working period of six months totaling 119 nurses. The analytical method used in this study is Structural Equation Model (SEM) using the Partial Least Square (PLS) approach. The results of this study indicate that job satisfaction has a positive and nonsignificant influence on turnover intentions; it means that job satisfaction is relatively high but cannot reduce the desire of nurses to leave. At the same time, organizational commitment negatively and significantly influences turnover intentions. Simultaneous test results greatly influence job satisfaction and corporate loyalty on turnover intentions. To keep the work situation conducive, hospital management can maintain and even improve the policies that have been implemented so far, namely policies that are increasingly profitable for nurses, one of which is performance appraisal for nurse members. Keywords: hospital, job satisfaction, nurses, organizational commitment, turnover intentions